Impact of soil moisture initialization on a simulated flash flood - Ashby, Christopher Travis, author (Colorado State University. Libraries, 2001)
On the evening of 28 July 1997, an extreme rainfall event in Fort Collins, Colorado produced severe local flooding. Over 25 cm (10 in) of this fell over southwest Fort Collins during the 5.5 hour period beginning at 1730 MDT July 28 and ending at 2300 MDT. The Regional Atmospheric Modeling System (RAMS) Ver. 3b is used to simulate this event. The focus of this research is to better understand the simulated mechanisms for extreme precipitation generation given differing initial conditions. The simulations utilize four telescopically nested grids allowing for resolution of synoptic-, meso-, and convective scale motions in the respective domains. The initial atmospheric fields were supplied from the Rapid Update Cycle (RUC) operational forecast model analysis, sounding data and surface observations corresponding to 12Z 28 July 1997. Two simulations were performed, differing only in the method of soil moisture initialization. Simulation A was initialized with the soil moisture fields taken from the operational 40-km ETA forecast model analysis, while Simulation B was initialized using the Antecedent Precipitation Index (API) method of soil moisture estimation. The synoptic scale forecasts show that Simulations A and B differ considerably in the boundary layer thermodynamic and wind predictions due to an overestimated evaporation fraction in regions of high soil moisture content in Simulation A. The primary difference in synoptic scale evolution between Sim. A and B is the intensity of the topographic circulation that results from a higher simulated low-level temperature in Sim. B. An accompanying increase and eastward shift in vertical mass transport relative to the Continental Divide, as well as increased Grid-2 precipitation volume are produced in Sim. B. Precipitation evolution is similar between simulations prior to 18002 followed by considerable differentiation in convective evolution after 18002. By 05002, 29 July, Simulation A produces a Grid-4 maximum accumulation of 26 cm (10.2 in.) 23-km to the southeast of Fort Collins. Simulation B generates two, Grid-4, maxima of 11 cm (4.33 in.) approximately 120-km to the southeast of Fort Collins and accumulations of 8-9 cm approximately 30-km to the south and southeast of Fort Collins. Additionally, Simulation B produces a larger area of accumulated precipitation greater than 1-cm. The differences in accumulated precipitation occur despite comparable precipitation rates (- 10-19 cm/hr) between simulations. Storm motion is identified as the primary contributing factor to the differences in accumulated precipitation. The time sequence of cell initiation locations in Simulation B is partially determined by the movement of the eastern edge of the storm-induced cold-pools. The theoretically predicted steady-state propagation speed for the cold-pool front is higher by a factor of 2.4 in Simulation B than in Simulation A during the quasi-stationary phase of the flood producing storm in Simulation A. This increase is due to the thermodynamic differences in the cold-pool environment rather than the cold-pools proper. During the quasi-stationary phase in Simulation A, the predicted steady state cold-pool propagation speed is within 0.8 mis of the upstream, lowest 200-m average windspeed. These results suggest that the low-level thermodynamic forecast differences, which are controlled by the soil moisture initialization, are physically related to the accumulated precipitation differences through the cold-pool influence on storm propagation.
Spring 2001.
Keywords: Flood; Floods -- Colorado -- Fort Collins; Soil moisture